Medical education research remains the poor relation. Issue 7615 (16th August 2007) - Todres, Mathew; Stephenson, Anne; Jones, Roger
Abstract : Research into medical education is stagnating and urgently needs the resources to become more rigorous and relevant say Mathew Todres, Anne Stephenson, and Roger Jones